Developing brand identity blueprint for a café bar - Kozlova, Olesia (2023)
This bachelor thesis deals with the creation of a corporate identity for the coffee place.The aim of this bachelor thesis is the creation of a functional brand design with a detailed description using the example of a particular specific company. The theoretical part describes what it takes to create a successful brand identity, how corporate design, culture and style are related and how this affects the product and the perception of the company. It also dedicates to outputting various types of logos, typography, and color palettes. At the beginning of the practical part, there is a thorough negotiation with the client to clearly define the goal and the expected results. Thereafter, the selected company, its current corporate identity and last but not least its competitors are described and analyzed in detail. It continues with the application of the knowledge from the theoretical part using the example of creating a completely unique brand identity. In the end, it displays the results in the form of a brand presentation.